MANAGERIAL CONSULTING IN THE SYSTEM OF INNOVATIVE ECONOMIC AND MANAGEMENT DEVELOPMENT - Е. А. Кузнєцов (Ринкова економіка: сучасна теорія і практика управління)
The article deals with the problems of managerial consulting as an important institution in the process of management professionalization and the formation of an innovation economy. Substantiates the position that the establishment of a professional management consulting creates the conditions for effective interaction between science, analytics and management practices. We study the factors of innovation management consulting.